2004
DOI: 10.5194/angeo-22-773-2004
|View full text |Cite
|
Sign up to set email alerts
|

High- and mid-latitude quasi-2-day waves observed simultaneouslyby four meteor radars during summer 2000

Abstract: Abstract.Results from the analysis of MLT wind measurements at Dixon (73.5 • N, 80 • E), Esrange (68 • N, 21 • E), Castle Eaton (UK) (53 • N, 2 • W), and Obninsk (55 • N, 37 • E) during summer 2000 are presented in this paper. Using S-transform or wavelet analysis, quasi-two-day waves (QTDWs) are shown to appear simultaneously at high-and mid-latitudes and reveal themselves as several bursts of wave activity. At first this activity is preceded by a 51-53 h wave with S=3 observed mainly at mid-latitudes. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…During that summer they also observed long-period 14-17-day wind oscillations of s ¼ 1. A similar observation except for 9-10-day wave instead of the 14-17-day wave was presented by Merzlyakov et al (2004) for summer 2000. These works implicitly or explicitly state the question: which of these waves are primary and which ones are secondary waves, respectively.…”
Section: Introductionsupporting
confidence: 74%
“…During that summer they also observed long-period 14-17-day wind oscillations of s ¼ 1. A similar observation except for 9-10-day wave instead of the 14-17-day wave was presented by Merzlyakov et al (2004) for summer 2000. These works implicitly or explicitly state the question: which of these waves are primary and which ones are secondary waves, respectively.…”
Section: Introductionsupporting
confidence: 74%
“…The modulation of the Q2DW by other planetary waves with longer periods and/or the interference between several coexisting spectral components (Merzlyakov et al, 2004) could be possible explanations of such behavior. The duration of a burst can vary from 3 to 10 cycles (6-20 days).…”
Section: Resultsmentioning
confidence: 98%
“…Observations of the 2-day wave have revealed that its amplitude maximises at middle to low latitudes in summer (e.g., Wu et al, 1996;Limpasuvan and Wu, 2003;Merzlyakov et al, 2004;Limpasuvan et al, 2005). At middle and low latitudes, the wave is composed primarily of westward-propagating zonal wavenumbers 3 and 4 (hereafter W3 and W4).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies made using ground-based radars have investigated the summertime mesospheric polar 2-day wave and have also revealed the existence of strong 2-day wave activity around the winter solstice at high latitudes (Nozawa et al, 2003a, b;Manson et al, 2004;Merzlyakov et al, 2004;Nozawa et al, 2005;Palo et al, 2007;Baumgaertner et al, 2008;Sandford et al, 2008). Nozawa et al (2003a) presented a climatology of the 2-day wave in the Arctic based on three years of observations at heights of 70-91 km made by an MF radar at Tromsø (69.6 • N, 19.2 • E).…”
Section: Introductionmentioning
confidence: 99%